ANALYSIS OF MEMORABLE EXPERIENTIAL MARKETING ON REPURCHASE INTENTION WITH BRAND AWARENESS AS A MEDIATING VARIABLE IN CAFÉS AND RESTAURANTS - Wahyudi, Falsa Shakira; Muhammad Danial, R. Deni; Komariah, Kokom (JURNAL MANAJEMEN MOTIVASI, 2025)
This study analyzes the effect of memorable experiential marketing on repurchase intention with brand awareness as a mediating variable among Butler Bar & Bistro consumers in Sukabumi. It uses a quantitative method with a causal associative approach and PLS-SEM analysis of 200 respondents. The results show that experiential marketing significantly influences both brand awareness and repurchase intention. Brand awareness also significantly affects repurchase intention and mediates the relationship. This study contributes theoretically and practically to marketing strategies in the café and restaurant sector.